Manajemen Mengurangi Kecemasan dan Nyeri dalam Persalinan dengan Menggunakan Virtual Reality : A review - Intan Gumilang Pratiwi; Herliana Riska; Kristinawati Kristinawati (JURNAL KEBIDANAN, 2019)
Labor pain is a subjective experience experienced by the mother about physical sensations associated with uterine contractions, dilation and thinning of the cervix and decreased fetus during labor. Reaction to pain is a very individual response. The sensitivity of anxiety in labor pain has a significant relationship to sensory and affective pain in labor. Labor anxiety and pain significantly affect maternal labor, therefore various methods of pharmacological and non-pharmacological methods are carried out in an effort to deal with pain. Technology was also developed to support these non-pharmacological efforts. One of them uses virtual reality (VR) as the current and future trends for pain management. This scientific article is a literature review with a systematical review method from various literature which includes a systematic search study of computerized databases (PubMed, BMC, Cochrain review, Google Scholar) in the form of research journals and review articles related to virtual reality. The results of this literature study are virtual reality technology capable of reducing anxiety and being able to be used to reduce pain during labor.